The Knowledge, Perception and Attitude of Year 1 Undergraduate Students in the Faculty of Medicine and Health Sciences (FMHS), Universiti Malaysia Sarawak (UNIMAS) on Coronary Artery Disease (CAD) - Saiful Bahri, Talip (UNIMAS Publisher, 2022)
Coronary Artery Disease (CAD) is a cardiovascular disease where there is plaque buildup in the wall of the coronary artery, an artery that supplies blood to the heart. This disease is also often referred to as coronary heart disease or ischemic heart disease. Globally and in Malaysia, CAD has been known as the most common type of heart disease and the leading cause of death. Hence, this study aims to determine the knowledge, attitude and perception of CAD among the students of the University of Malaysia, Sarawak (UNIMAS). The minimum number of Year 1 FMHS students involved in this study was calculated by using Raosoft Sample Size Calculator software. A Google online form (self- administered questionnaire) that consisted of respondent’s characteristics, perception of CAD, knowledge on risk factors and clinical presentation of CAD, and attitude towards the preventive measure of CAD was used to collect the data. The data collected was analyzed by using IBM SPSS Statistics software version 27 while the frequencies, means, standard deviation, and p-value were calculated to achieve the specific objectives of this study. According to the results, out of 200 respondents, most of the respondents were female (76.5%) and participation from medical students (66.5%) was more than the nursing students (33.5%). Overall, females have a better level of knowledge on CAD compared to males. Nursing students have a better level of attitude towards the preventive measure of CAD than medical students while medical students have a higher level of knowledge on other parts of the questionnaire compared to nursing students. There is a significant correlation between the perception of CAD, its risk factors, clinical presentation, and the attitude towards the preventive measure of CAD. Knowledge of CAD clinical presentation and preventive measures has a significant correlation with the gender of the respondents. Meanwhile, the knowledge of risk factors of CAD has a significant correlation with the courses of the students. However, the perception of CAD does not have a significant correlation with both gender and the courses of the students. Furthermore, the results obtained from the study may not represent the level of knowledge regarding CAD on a large scale. Therefore, more research regarding this issue should be conducted more often as it will help to give an even better overview of the level of knowledge about CAD and its association with the attitude on CAD preventive measures among the community.